AUDIT INTERNAL SISTEM INFORMASI AKUNTANSI PENGELOLAAN ALOKASI DANA DESA (ADD) UNTUK MENILAI AKUNTABILITAS KINERJA DESA (Di Desa Batokan Kecamatan Kasiman Kabupaten Bojonegoro) Tahun 2015 - Purnama, Davis Budi; Widiastoeti, Hendy (JEB17 : Jurnal Ekonomi dan Bisnis, 2016)
Internal audit of accounting information system in the village of Batokan, did in the subdistrict Kasiman, Bojonegoro Regency aims to acknowledge and identify the problems related to the management of the allocation of the funds of the village mainly on planning, implementation, and accountability. As well as providing accounting information system management of the allocation of the village Fund, so that the performance of the village of Batokan in the management of the village fund allocation can achieve performance accountability of Government Agencies, has the Government agency performance accountability system, as well as generate accountability refers to the report of the performance accountability of agencies of Government.The methods used in this research is qualitative method. Data obtained by means of field studies through the interview process, documentation and observation. The process of data analysis used is making the accounting information system of managing the allocation of funds the village using data flow diagram (flowchart) and classify the conditions, criteria, cause and effect.Based on the results of the research that has been analyzed as a whole then it can be inferred that the performance of the village Batokan in the management of the allocation of the village Fund insufficient. As for some of the weakness in the village of Batokan, among others, the village government apparatus limited ability in managing the allocation of funds, the submission and reporting accountability that is insufficient and has yet to effectively report on accountability for the realization of the village Fund allocations to the community.Based on the results of the findings about the problems on the face, then given some suggestions and recommendations to enhance accountability of the performance of the village Batokan in terms of the management of the allocation of the funds of the village in the future.Keywords: Internal Audit, Accounting Information Systems, The Management of the Village Fund Allocation, Performance Accountability Village.